2008
DOI: 10.21273/hortsci.43.6.1813
|View full text |Cite
|
Sign up to set email alerts
|

Growth Pattern and Phenological Stages of Early-maturing Peach Trees Under a Mediterranean Climate

Abstract: The phenological stages of early-maturing peach trees were described using the traditional nomenclature of Baggiolini and according to the BBCH General Scale. The heat requirement of each stage was calculated as growing degree hours (GDH) and growing degree days (GDD). The annual growth pattern of trunk, shoot, and fruit was also studied. After dormancy breaking involving 225 chilling units, this early peach cultivar required ≈6244 GDH to reach full bloom and 27106 GDH before the fruit could be harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 22 publications
8
41
0
2
Order By: Relevance
“…Although blooming and harvesting time may change every year depending on the environmental conditions, especially temperature (Sánchez-Pérez et al 2007;Mounzer et al 2008;Ruiz and Egea 2008), the fruit development period (number of days from full bloom to maturity) remained more or less stable for each seedling over the 3 years of study (data not shown). The peach fruit development period is highly dependent on cultivar (Jackson and Sherman 1980;Muñoz et al 1986;Cunha et al 2007;Cheng 2008;Mounzer et al 2008), however, previous research has shown an influence of spring temperatures on the harvest date of peach cultivars (López and DeJong 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although blooming and harvesting time may change every year depending on the environmental conditions, especially temperature (Sánchez-Pérez et al 2007;Mounzer et al 2008;Ruiz and Egea 2008), the fruit development period (number of days from full bloom to maturity) remained more or less stable for each seedling over the 3 years of study (data not shown). The peach fruit development period is highly dependent on cultivar (Jackson and Sherman 1980;Muñoz et al 1986;Cunha et al 2007;Cheng 2008;Mounzer et al 2008), however, previous research has shown an influence of spring temperatures on the harvest date of peach cultivars (López and DeJong 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The peach fruit development period is highly dependent on cultivar (Jackson and Sherman 1980;Muñoz et al 1986;Cunha et al 2007;Cheng 2008;Mounzer et al 2008), however, previous research has shown an influence of spring temperatures on the harvest date of peach cultivars (López and DeJong 2007). Very early-maturing, as well as very late-maturing peach genotypes, are of considerable interest for the peach industry in the Mediterranean area (Caruso and Sottile 1999), and the main difference between these genotypes is the length of their fruit development period (Mounzer et al 2008). In the present work, the fruit development period ranged from 80 to 130 days for all the progenies, except for 'Andross' 9 'Calante' which showed the longest period (approximately 150 days).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In peach trees, water deficits during the second fruit rapid growth phase are more harmful than in other phenological stages (Besset et al, 2001;Naor et al, 2005), and the postharvest phase is the most suitable period for applying irrigation deficits Mounzer et al, 2008). For the implementation of regulated deficit irrigation strategies, crop critical periods, the overlapping stages of vegetative and fruit growth and the exact plant response to water deficits under local conditions must be understood (Abrisqueta et al, 2010;Girona et al, 2003;Girona et al, 2005).…”
Section: Introductionmentioning
confidence: 99%